AB0271 Changes of serological markers in early and established rheumatoid arthritis (RA) during the course of traditional and biological disease modifying therapy. (23rd January 2014) - Böhler, C.; Radner, H.; Studenic, P.; Smolen, J.S.; Aletaha, D.
Abstract : Background: Rheumatoid factor (RF) and antibodies to citrullinated peptides (ACPA) are established markers in the diagnostic and prognostic approach to RA 1 . Several studies have examined changes of RF during therapy, but data for ACPA are controversial and scarce, and the effects of RA chronicity are still not completely understood 2 . Objectives: To investigate the influence of treatment response and disease duration on RF and ACPA levels. Methods: We obtained data of outpatients from a long-term observational database with prospective data entry. We retrieved clinical and serological data of patients treated with methotrexate, leflunomide and/or TNF inhibitors from the treatment start through six months of therapy. For analyses of the effects of treatment response and duration of RA, we calculated the SDAI 50% response at 6 months, and divided the patients into early (≤6 months duration) and established RA (>6 months). We used the Spearman test (r) to analyse correlations between changes in SDAI and changes in autoantibody levels. RF was determined by nephelometry (upper limit of normal [ULN] 14IU/ml) and ACPA by anti-CCP ELISA (ULN: 5U/ml). Only patients with complete datasets for the whole 6 months were selected. Results: 96 RF and ACPA positive patients were included. Autoantibody levels declined significantly over the 6 months of therapy for both, RF (p=0.01) and ACPA (p=0.05). Treatment responders and patients with short disease duration showed the greatest changes (Table). There was no significant difference in the distribution of relative changes in RF and ACPA (p=0.99). Changes of SDAI correlated significantly with those of RF (r=0.32; p=0, 01) and ACPA (r=0.25; p=0, 05), particularly in early stages of RA (RF: r=0.52; p=0, 05 and ACPA: r=0.59; p=0, 01). Conclusions: RF and ACPA levels decreased in line with the clinical response, especially at early stages of RA. Further research is needed to analyse the impact of early serological changes on the long-term outcome of RA. References: Song YW, Kang EH. Autoantibodies in rheumatoid arthritis: rheumatoid factors and anticitrullinated protein antibodies. QJM 2010;103(3):139-46. Bobbio-Pallavicini F, Caporali R, Alpini C, Moratti R, Montecucco C. Predictive value of antibodies to citrullinated peptides and rheumatoid factors in anti-TNF-alpha treated patients. Ann N Y Acad Sci 2007;1109:287-95. Aletaha D, Martinez-Avila J, Kvien T, Smolen J. Definition of Treatment Response in Rheumatoid Arthritis Based on the Simplified and the Clinical Disease Activity Index. [abstract]. Arthritis Rheum 2011;63 Suppl 10:2226. Disclosure of Interest: None Declared